(untitled) (International Journal of Physiotherapy, 2025)
Background: Ankle sprains are common during sports that involve frequent directional changes and, therefore, require efficient training regimens for joint stability and prevention of injuries. The purpose of this study is to examine the effects of sprint-plyometric training with varying directional change frequencies on ankle joint function and the prevention of lateral ankle sprains in recreationally active adults. Methods: Ninety volunteers (45 Male and 45 Female), aged between 18 and 35 years, were allocated to High-Frequency Directional Change (HFDC, n=30), Moderate-Frequency Directional Change (MFDC, n=30), and Control (n=30) for a 12-week intervention. Outcomes included ankle joint stiffness (isokinetic dynamometry), proprioception (joint position sense via motion capture), neuromuscular activation (electromyography), biomechanical parameters (kinematics, ground reaction forces), and injury incidence (Poisson regression). Group × time interactions were quantified using linear mixed models, reporting effect sizes (Cohen’s d) and percentage changes. Results: The HFDC group demonstrated significant gains in ankle stiffness (31.1–31.6%, d=1.33–1.39, p<0.001), proprioception (52.0–56.5% error decrease, d=1.39–1.75, p<0.001), and neuromuscular activation (38.3–48.0% EMGincrease, d=1.26–1.45, p<0.001). Biomechanical changes consisted of decreased inversion angles (33.3%, d=1.73, p<0.001) and lateral ground reaction forces (28.6%, d=1.60, p<0.001). There were no sprains experienced by the HFDC group (0 per 1000 hours) compared to 1.85 (MFDC) and 7.41 (Control) per 1000 hours (IRR=0.00, p<0.001). Females had larger proprioceptive improvements (d=1.89 vs. 1.60, p=0.028). Conclusion: High-frequency directional change training significantly improves ankle function and avoids sprains, providing a strong strategy for sports with multi-planar movements.